2002
DOI: 10.1007/bf03020428
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial subdural hematoma after unintended durotomy during spine surgery

Abstract: Purpose: To report a case of intracranial subdural hematoma occurring after a spinal dural tear that was made unintentionally during the course of a posterior laminectomy and spinal fusion at the L 5 -S 1 level. The possible physiopathological mechanisms are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 11 publications
0
28
1
Order By: Relevance
“…Failure to achieve watertight dural closure not only can increase the incidence of spinal headache, nausea, and vomiting immediately after surgery, 23,28,33 but may also predispose patients to more serious postoperative complications such as CSF leakage, CSF-cutaneous fistula, pseudomeningocele, wound infection, meningitis, and even intracranial hemorrhage. 1,14,17 Some methods of MIS dural closure have been described in the literature. Chou et al 4 reported a technique for MIS primary dural repair using a micropituitary rongeur as the needle holder in combination with a laparoscopic knot pusher commonly used in arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to achieve watertight dural closure not only can increase the incidence of spinal headache, nausea, and vomiting immediately after surgery, 23,28,33 but may also predispose patients to more serious postoperative complications such as CSF leakage, CSF-cutaneous fistula, pseudomeningocele, wound infection, meningitis, and even intracranial hemorrhage. 1,14,17 Some methods of MIS dural closure have been described in the literature. Chou et al 4 reported a technique for MIS primary dural repair using a micropituitary rongeur as the needle holder in combination with a laparoscopic knot pusher commonly used in arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9,19,39 However, serious complications, such as neurological deficit, pseudomeningocele, meningitis, and intracranial hemorrhage, have been reported. 4,5,7,11,14,20,[23][24][25][26][27][28]34,42 In addition, rates of persistent CSF wound leak and pseudomeningocele formation have been reported to be as high as 17.6%. 15 In our series of patients with a mean follow-up of 310 days, there were no complications referable to durotomy, which compares favorably with the current literature on durotomies after open cases.…”
Section: Discussionmentioning
confidence: 99%
“…The result is a SSDH due to intracranial hemorrhage and migration of blood into the spinal subdural space, facilitated by CSF hypovolemia and gravity [20][21][22][23][24][25][26][27][28][29][30][31][32]. This pathophysiology is also cited for SSDH, after incidental durotomy associated with CSF leak [33][34][35].…”
Section: Discussionmentioning
confidence: 99%